2013
DOI: 10.1292/jvms.12-0487
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of an H5N1 Highly Pathogenic Avian Influenza Virus Isolated in the 2010–2011 Winter in Japan to Mandarin Ducks

Abstract: ABSTRACT. Widespread outbreaks of highly pathogenic avian influenza (HPAI) caused by H5N1 viruses occurred in wild birds in Japan from 2010-2011. Forty out of 63 deceased wild birds belonged to the order Anseriformes, and mandarin duck was one of the dominant species. To estimate the risk of mandarin ducks as a source of virus infection in the environment, we examined the pathogenicity of a causal H5N1 HPAI virus to mandarin ducks. About half of the mandarin ducks died by inoculation with 10 7.0 TCID 50 of A/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…In Yamaguchi, two outbreaks occurred in 2004 and 2014 near the area where wild boars were captured [5, 10]. AIV H5N1 is thought to be transferred by birds migrating from the Asian continent to Japan and has been introduced into poultry farms, causing lethal infections [17]. Therefore, we suspected that AIV H5N1 might be more prevalent in Japan, including at Yamaguchi.…”
mentioning
confidence: 99%
“…In Yamaguchi, two outbreaks occurred in 2004 and 2014 near the area where wild boars were captured [5, 10]. AIV H5N1 is thought to be transferred by birds migrating from the Asian continent to Japan and has been introduced into poultry farms, causing lethal infections [17]. Therefore, we suspected that AIV H5N1 might be more prevalent in Japan, including at Yamaguchi.…”
mentioning
confidence: 99%
“…Most of the ducks dying from infection showed neurological signs, suggesting that the death of these ducks was likely to be associated with damage in the central nervous system. The results obtained in this study seem to be consistent with the previous studies performed for the H5N1 HPAIV of clade 2.3.2.1 isolated from wild birds until 2011 (Kwon at al., 2011; Sakoda et al, 2010; Soda et al, 2013), confirming that the H5N1 isolate of clade 2.3.2.1 could cause illness and death in a large proportion of domestic ducks.…”
Section: Discussionmentioning
confidence: 73%
“…In 2012, viruses of clade 2.3.2.1 were dominantly circulating in Vietnam. Several studies reported on the pathogenicity of H5N1 viruses of clade 2.3.2.1, which were isolated from wild birds until 2011 (Kwon et al, 2011; Sakoda et al, 2010; Soda et al, 2013). However, pathogenicity of the H5N1 HPAIV isolated from domestic ducks in Vietnam in 2012 has not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the H5N8 subtype occurring in 2014–2016 caused relatively mild clinical symptoms in duck species, compared with the H5N6 subtype in the 2016–2017 epidemic ( 19 ). In contrast, the H5N1 subtype that affected poultry holdings during the 2010–2011 epidemic was lethal to domestic ducks ( 20 ). Furthermore, the basic reproduction number, which estimates the average number of infectees by a single infector, was the highest in H5N1 compared to subtype H5N8 and H5N6 ( 21 ).…”
Section: Introductionmentioning
confidence: 99%